ARHGEF18/p114RhoGEF Coordinates PKA/CREB Signaling and Actomyosin Remodeling to Promote Trophoblast Cell-Cell Fusion During Placenta Morphogenesis - Beal, Robert; Alonso-Carriazo Fernandez, Ana; Grammatopoulos, Dimitris K.; Matter, Karl; Balda, Maria S. (Frontiers in Cell and Developmental Biology, 2021)
Coordination of cell-cell adhesion, actomyosin dynamics and gene expression is crucial for morphogenetic processes underlying tissue and organ development. Rho GTPases are main regulators of the cytoskeleton and adhesion. They are activated by guanine nucleotide exchange factors in a spatially and temporally controlled manner. However, the roles of these Rho GTPase activators during complex developmental processes are still poorly understood. ARHGEF18/p114RhoGEF is a tight junction-associated RhoA activator that forms complexes with myosin II, and regulates actomyosin contractility. Here we show that p114RhoGEF/ ARHGEF18 is required for mouse syncytiotrophoblast differentiation and placenta development. In vitro and in vivo experiments identify that p114RhoGEF controls expression of AKAP12, a protein regulating protein kinase A (PKA) signalling, and is required for PKA-induced actomyosin remodelling, cAMP-responsive element binding protein (CREB)-driven gene expression of proteins required for trophoblast differentiation, and, hence, trophoblast cell-cell fusion. Our data thus indicate that p114RhoGEF links actomyosin dynamics and cell-cell junctions to PKA/CREB signalling, gene expression and cell-cell fusion.